2013
DOI: 10.1158/1078-0432.ccr-13-0018
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Feedback of the HIF-1α Pathway via Interferon-Stimulated Gene 15 and ISGylation

Abstract: Purpose: The IFN-stimulated gene 15 (ISG15)-and ubiquitin-conjugation pathways play roles in mediating hypoxic and inflammatory responses. To identify interaction(s) between these two tumor microenvironments, we investigated the effect of ISG15 on the activity of the master hypoxic transcription factor HIF-1a.Experimental Design: IFN and desferoxamine treatments were used to induce the expression of ISGs and HIF-1a, respectively. Interactions between HIF-1a and the ISG15 and ISGylation system were studied usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 51 publications
(85 reference statements)
4
43
2
Order By: Relevance
“…Cancer cells treated with TGF-β undergo EMT. We investigated the mechanism underlying TGF-β-induced EMT in A549 (lung), HeLa (cervical), and 769-P (renal) cancer cells, all of which have been established as suitable models for studying EMT in vitro (12)(13)(14)(15). As expected, TGF-β treatment resulted in the acquisition of spindle-fibroblastic morphology, downregulation of epithelial marker E-cadherin, and upregulation of mesenchymal markers fibronectin (FN), vimentin and N-cadherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells treated with TGF-β undergo EMT. We investigated the mechanism underlying TGF-β-induced EMT in A549 (lung), HeLa (cervical), and 769-P (renal) cancer cells, all of which have been established as suitable models for studying EMT in vitro (12)(13)(14)(15). As expected, TGF-β treatment resulted in the acquisition of spindle-fibroblastic morphology, downregulation of epithelial marker E-cadherin, and upregulation of mesenchymal markers fibronectin (FN), vimentin and N-cadherin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transient transfections of cancer cell lines were performed using Lipofectamine 2000 (Invitrogen). Whole cell extracts were prepared at specific time-points after transfection and subjected to SDS-PAGE/western blotting or immunoprecipitation assays as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, ISG15 is elevated upon traumatic brain injury (Rossi et al, 2015) and after cerebral focal ischemia (Nakka et al, 2011), where it has a neuroprotective effect as shown by increased mortality, exacerbated infarction and worsened neurologic recovery of ISG15-KO mice when they are subjected to transient middle cerebral artery occlusion (Nakka et al, 2011). Interestingly, ISGylation of hypoxia-inducible factor 1α (HIF-1α) disrupts its dimerization and attenuates HIF-1α-mediated gene expression, resulting in decreased tumor growth (Yeh et al, 2013). Furthermore, ISGylation is activated during erythroid differentiation, with a significant decrease in the proportion of fully differentiated erythrocytes and a concomitant increase in the proportion of erythroid precursors in ISG15-KO mice (Maragno et al, 2011).…”
Section: Newly Described Isg15 Functionsmentioning
confidence: 99%
“…Microarray studies of muscle biopsies from patients with DM have shown overexpression of IFN-I-inducible transcripts, such as interferon-inducible protein 15 (ISG15), Myxovirus resistance A (MxA), Signal Transducer and Activator of Transcription 1 (STAT1) and retinoic acid-inducible gene I (RIG-I), that were validated at the protein level and specifically detected at perifascicular atrophic areas in DM muscle 10 – 14 . Interestingly, it has been shown that ISG15 bears HREs in its promoter and a negative feedback loop for HIF-1α in some cell lines has been proposed 15 . RIG-I is an innate immunity receptor of the retinoic acid-like receptors family and an IFN-stimulated gene itself 16 .…”
Section: Introductionmentioning
confidence: 99%